Design of motorcycle safety helmet for children in Malaysia - Ong, Wei Yang (2001)
The first part of the study is undertaken to investigate the need for a motorcycle safety helmet for children. From the field observations and interviews conducted, it was found that the current situation warrants the need for a motorcycle safety helmet for children to be developed. Motorcycle safety helmet, as an injury control device is used to curb the high fatality rate associated with head injuries among motorcycle users. In addition, a field study was conducted to investigate the design parameters of the helmet. A head size of 570mm in circumference was selected based on the size that fits the maximum number of users and the availability of the test head form sizes. It was found that a lighter helmet is generally preferred from the comfort viewpoint. The second part of the study involves the design of the motorcycle safety helmet for children. A finite element model of the children motorcycle safety helmet for impact test was developed using Hypermesh, a pre-processor. LS-DYNA, a finite element code was used to simulate the impact response of the helmet. The model was validated using an indirect inference approach. The results clearly indicate that the model correlated well with the experimental results from literatures. A simple parametric study was carried out to investigate the effect of varying thicknesses of the Acrynonitrile Butadiene Styrene (ABS) shell and the Expanded Polystyrene (EPS) foam. It was found that the typical thicknesses of the shell and foam provide the best compromise between the shock absorbing performance and the design constraints. None of the eight impacts simulated in accordance to the MSI 1996 type test resulted in an acceleration exceeding the permissible level of 300g. From the simulations, the helmet impact deformation mechanisms were discussed. It is recommended that future research to be carried out to further improve the design of the motorcycle safety helmet and to study the possible ventilation systems. In addition, it is suggested that a more stringent form of verification to be undertaken to validate the FE model of the helmet.